VAKSINASI LANSIA UPAYA PREVENTIF MENINGKATKAN IMUNITAS AKIBAT PROSES PENUAAN - Susanti, Nurlaili (El-Hayah : Jurnal Biologi, 2014)
Advancement in health sciences and technologies gives positive impact to improve life expectancy, but the other hand it can increases elderly population with all consequences. Old age is associated with high morbidity and mortality due to their susceptibility to suffer several diseases caused by lacking immunity, especially infectious diseases. Moreover, the occurrence of multiple morbidities, such as heart disease and vulnerability to stress, are the main confounding factors that may impact to immune functions of elderly. Aging affects both cellular and humoral responses of the innate and adaptive immune systems and causes decreasing the number of immune cells, their viability, functional capacity and their responses against pathogens that entering the body. Strategies for preventing these diseases would have a clear impact on improving healthy aging. Thus, vaccination strategies for elderly population are needed. Vaccines should be developed to take into consideration the peculiar age-induced variations of immune responsiveness